SIMULASI MODEL ISING 2D DENGAN FAKTOR MEDAN MAGNET DAN TEMPERATUR MENGGUNAKAN IMAGEJ - , faradiba; , Dr. Rinto Anugraha, NQZ. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to simulate the two dimensional Ising spin using Monte Carlo method with Metropolis algorithm. The programs are written in macro language and ran in ImageJ software. In the absence of external magnetic field, some physical observables such as energy and magnetization are measured as functions of temperature and system size. Therefore, for a certain system size namely 128 x 128, we calculated both specific heat capacity and susceptibility as functions of temperature. We found that for low temperature regime, the absolute magnetization close to 1, which means that all spins are in the homogeneous state. By the increase the temperature close to the critical one = 2,3 J/kB, the magnetization decrease drastically into zero. For the energy, low temperature regime gives the low energy. By the increase the temperature, the energy increase drastically near the critical temperature, and finally close to zero for high temperature regime. The role of the critical temperature appears significantly indicated by both specific heat capacity and susceptibility. Both observables have very high values in the critical temperature. In the presence of the external magnetic field, we vary the magnitude of the field and measure the magnetization. We found that the hysteresis of the magnetizations appears. Later, we determine both remanent magnetization and coercive field for a certain temperature. We found that both tend to decrease by the increase of the temperature. Using the sinusoidal and square waves of the external field, we found that the profile of the magnetization is similar to that of the external field. However, we found the time lag between the two profiles. Moreover, we measure the time lag between the magnetization and the external field and reveal that time lag decrease for the increase of the amplitude of the external field.